Examining Justice! The Double Burden of Women in Indonesia from the Perspective of The Compilation of Islamic Law - Qothrunnada, Qonita; Maghfur, Asy Syifak Qolbi; Kushidayati, Lina (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2024)
This study investigates the phenomenon of the double burden faced by women in Indonesia through the lens of the Compilation of Islamic Law (Kompilasi Hukum Islam, KHI). The double burden refers to the dual roles that women fulfill, balancing responsibilities within the household and in the public workforce. Utilizing a qualitative approach and document analysis, this research explores how the KHI addresses women’s roles and responsibilities in both spheres. Real-life cases of Indonesian women are examined to assess how interpretations of the KHI impact their experiences. Findings indicate that while the KHI acknowledges women’s participation in multiple facets of life, its implementation is often constrained by patriarchal interpretations that lack gender sensitivity. This has resulted in women bearing disproportionate responsibilities at home and work. The study underscores the need for a more progressive reinterpretation of the KHI to reduce the double burden on women, promoting gender equality and enhancing women’s welfare in Indonesia. These insights are intended to inform strategies for advancing gender equity within the framework of the KHI, contributing to broader social and legal reforms.